2011
DOI: 10.1002/ijch.201100026
|View full text |Cite
|
Sign up to set email alerts
|

The Reduction of Dioxygen by Keggin Heteropolytungstates

Abstract: Reversible redox chemistries are an inherent feature of numerous metal oxide cluster anions (POMs). Moreover, as discrete molecular structures with well‐defined and controllable solution chemistries, POMs can be deployed as physicochemical probes for studying inorganic reaction mechanisms. In the past decade, we have used an iso‐structural series of α‐Keggin heteropolytungstate cluster anions to systematically investigate a number of fundamental topics, including electron transfer to dioxygen. The iso‐structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 115 publications
(141 reference statements)
0
6
0
Order By: Relevance
“…A multitude of polyoxometalate (POM)-catalyzed O 2 -based oxidation reactions have been studied, and several of these processes have been commercialized. These are a subset of catalytic O 2 -based oxidation processes that continue to be heavily investigated because of their environmental attractiveness and potential low cost. POMs afford several advantages as oxidation catalysts, including the ability to address the low reactivity of O 2 in the ground state, readily store a single electron at a controllable potential, and function as highly effective ligands (carbon-free, multidentate, and synthetically tunable) for d-electron-metal(s) active sites. , ,, A central feature of these O 2 /air-based oxidation processes is the reaction of the reduced POM (POM red ) with O 2 . ,, This step is frequently much slower than oxidation of the substrate by the oxidized (resting oxidation state) POM (POM ox ) to form POM red . , Given this fact, it is surprising that major efforts have not been expended to find catalysts for the bottleneck POM red + O 2 step.…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of polyoxometalate (POM)-catalyzed O 2 -based oxidation reactions have been studied, and several of these processes have been commercialized. These are a subset of catalytic O 2 -based oxidation processes that continue to be heavily investigated because of their environmental attractiveness and potential low cost. POMs afford several advantages as oxidation catalysts, including the ability to address the low reactivity of O 2 in the ground state, readily store a single electron at a controllable potential, and function as highly effective ligands (carbon-free, multidentate, and synthetically tunable) for d-electron-metal(s) active sites. , ,, A central feature of these O 2 /air-based oxidation processes is the reaction of the reduced POM (POM red ) with O 2 . ,, This step is frequently much slower than oxidation of the substrate by the oxidized (resting oxidation state) POM (POM ox ) to form POM red . , Given this fact, it is surprising that major efforts have not been expended to find catalysts for the bottleneck POM red + O 2 step.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen from Scheme 1 the reaction of H 5 PV 2 Mo 10 O 40 (the oxidized compound, 1 ox ) with substrates either by an ET dehydrogenation or an ET-OT oxygenation is intrinsically a two-electron process. However, self-exchange ET between polyoxometalates is fast, 2,15,17 (1 red1e ). According to our calculations, this interaction is exergonic by 3.73 kcal mol À1 in acetonitrile and is favoured kinetically by the strong acidic nature of the surface protons.…”
Section: Kinetics Of Aerobic Oxidationmentioning
confidence: 99%
“…It has thus been shown that a Fe(II)-substituted polyoxotungstate binds O 2 , 14 but more generally the re-oxidation of reduced polyoxotungstates with O 2 in water has been shown to proceed by an outer-sphere electron transfer (ET). [15][16][17] The mechanism is less clear in the case of phosphovanadomolybdates. Moreover, although the redox potentials for different a-Keggin polyoxometalates show the following general trend, polyoxotungstates o polyoxomolybdates o polyoxovanadomolybdates, 18 the rates of their aerobic re-oxidation are not correlated with the redox potential: polyoxotungstates (seconds) c polyoxovanadomolybdates (minutes) c polyoxomolybdates (days).…”
Section: Introductionmentioning
confidence: 99%
“…Polyoxometalate (POM)-based redox processes underlie analytic methods such as phosphate determination, POM-based high-charge-capacity batteries, wet oxidation of organics, and most importantly, catalysts for O 2 -based oxidations. Several of the last species have been commercialized. , O 2 -based oxidation processes continue to be a mainstay in catalysis because of their green aspects and potential low cost. POMs display several advantages as oxidation catalysts: they can serve as effective, reversibly reducible, multidentate ligands for incorporation of one or more redox-active transition metals, which in turn, can help control the reactivity of ground-state triplet O 2 . ,,,,, A common barrier in these O 2 /air-based oxidation processes is reaction of the reduced POM (POM red ) with O 2 . ,, This step is usually slower than oxidation of the substrate by the resting oxidation state POM (POM ox ) to form the reduced POM. , Importantly, some of the most potentially useful POM oxidants (frequently those with the highest redox potentials such as the two targeted in this study, α-PW 12 O 40 3– and α-SiVW 11 O 40 5– ), are rendered marginally useful because their reduced forms cannot be reoxidized by O 2 /air at a satisfactory rate or at all in the studies to date.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated the highly efficient catalysis by submicromolar concentrations of Cu of the reaction between reduced Keggin polyoxometalates, POM red , and dioxygen . The mechanism of this POM red + O 2 reaction specifically for the reduced α-Keggin anions α-X n + W 12 O 40 (9– n )– (X = Al 3+ , Si 4+ , P 5+ ; 1 red , 2 red , and 3 red , respectively) was studied in detail because these POMs have been thoroughly characterized and known to be quite stable, nonprotonated, and non-ion-paired under the conditions in this paper and over a wide pH range. ,, Examination of the kinetics of this catalytic reaction at pH 2.0 in sulfate and phosphate buffers led to a proposed mechanism that entails the reversible reduction of Cu­(II) to Cu­(I) by POM red followed by a fast reoxidation of Cu­(I) to Cu­(II) by O 2 .…”
Section: Introductionmentioning
confidence: 99%